Urban Circular Economy in China: A Review Based on Chinese Literature Studies. (4th March 2021) - Su, Fang; Chang, Jiangbo; Li, Xi; Zhou, Dan; Xue, Bing
Abstract : Circular economy is a critical approach to realize the coordinated development of society, economy, and ecological environment. Given the fact that urban is a complex system in which human beings integrate material, energy, information, and natural environment and interact and influence each other, reviewing the urban circular economy research and development could benefit for having a better and comprehensive understanding on urban complexity. Mainly based on the Chinese literature studies from 1999 to 2020, this study aims to present an in-depth analysis of the research themes, policy systems, and index system of Chinaʼs urban-scale circular economy, discuss the changes and evolution trends of themes, levels, and perspectives in time series, sort out the policy systems at both the national and local levels, and analyze the design principles and application fields of indicators. Finally, we propose that future development of an urban circular economy should be built based on modern techniques, technologies, and models. The construction of development mechanism on the circular economy should be framed as "government-led, market-driven, legal norms, policy support, technological support, and public participation" and inject concepts such as "Internet +, " "sharing economy, " "Internet of Things, " and "artificial intelligence."